Colonialism is like Alligator weed - Jayson Cooper (2025)
This research podcast critically examines the role of educators in addressing the ongoing legacies of colonialism in Australian education. It argues that to be responsive, educators must engage in deep listening—not just to what is convenient, but to the difficult truths of colonial occupation, dispossession, and Indigenous survival. Examining the persistence of colonial narratives in curriculum and pedagogy, this podcast demonstrates how Australian education has historically reinforced a Eurocentric national identity while marginalising First Nations perspectives. Using metaphors such as invasive species to illustrate the self-perpetuating nature of colonialism, it highlights the structural mechanisms that sustain inequity, including policies that continue to disadvantage First Nations peoples. Through reflections on lived experiences, the research underscores the resistance of Indigenous communities and the responsibilities of educators to challenge structural racism, unlearn dominant narratives, and create spaces for Indigenous knowledges. It advocates for slow, relational decolonisation, positioning education as a site of both colonial entrenchment and potential transformation. This podcast calls for a reimagining of Australian education—one that moves beyond tokenistic inclusion to genuine engagement with Indigenous histories, knowledges, and futures.